Aquatic insect functional feeding groups in a mountain stream with a series of check dams in Northern Thailand - Phuchiwan Suriyawong (2018)
© 2018 Penerbit Universiti Kebangsaan Malaysia. All rights reserved. A series of check dams (or small dams in shallow streams) have been placed on many streams throughout Thailand and the number of them continue to increase. Check dam construction activities have been emphasized by the government and private sector entities over the last decade to prevent severe flood or drought due to changes in rainfall patterns. This study evaluated distribution of functional feeding groups (FFG) in a stream with a high density of check dams. Twelve sampling sites at three altitudes (500, 900 and 1500 m asl) included undammed and nearby dammed sections (above and below check dams) were used. Aquatic insects were collected monthly at each site for a year and categorized into FFG. Aquatic insect composition of undammed and above dam sites was different. Abundance within each FFG at above dam sites significantly differed from undammed sites. Taxonomic richness at 1500 and 900 m altitudes was decreased at above dam sites compared with the corresponding undammed sites, whereas above dam sites of 500 m altitude had higher richness than undammed site. High abundance of predators and collector-gatherers associated with reservoirs and fine sediment accumulation above dams, where filter-feeders were scarce. Shredder abundance varied among sites and was highest where leaf packs were most abundant. Scrapers were least abundant group and inconsistent with the dams. Distribution of FFG was similar to changes in other regulated streams. The composition of FFG reflected the stream ecosystem conditions through adaptation of communities to stream habitat and food resources, including those associated with check dam construction.